2012
DOI: 10.1029/2011jd016760
|View full text |Cite
|
Sign up to set email alerts
|

In situ observations of volcanic ash clouds from the FAAM aircraft during the eruption of Eyjafjallajökull in 2010

Abstract: During April–May 2010 the UK Facility for Airborne Atmospheric Measurements (FAAM) BAe‐146 aircraft flew 12 flights targeting volcanic ash clouds around the UK. The aircraft observed ash layers between altitudes of 2–8 km with peak mass concentrations typically between 200–2000μg/m3, as estimated from a Cloud and Aerosol Spectrometer (CAS). A peak value of 2000–5000 μg/m3 was observed over Scotland on 14 May 2010, although with considerable uncertainty due to the possible contamination by ice. Aerosol size dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 100 publications
(175 reference statements)
5
115
0
2
Order By: Relevance
“…For volcanic ash particles we use a mono modal log-normal distribution with a width of 1.7 σ , minimal radius of 0.1 µm and maximum radius of 5 µm. This values are similar to the outcome of inverted lidar and photometer data from Gasteiger et al (2011) or aircraft in-situ measurements (Johnson et al, 2012;Schumann et al, 2011).…”
Section: In Propertiessupporting
confidence: 70%
See 1 more Smart Citation
“…For volcanic ash particles we use a mono modal log-normal distribution with a width of 1.7 σ , minimal radius of 0.1 µm and maximum radius of 5 µm. This values are similar to the outcome of inverted lidar and photometer data from Gasteiger et al (2011) or aircraft in-situ measurements (Johnson et al, 2012;Schumann et al, 2011).…”
Section: In Propertiessupporting
confidence: 70%
“…Ansmann et al, 2010;Gross et al, 2012;Seifert et al, 2011) and aircraft (e.g. Johnson et al, 2012;Schumann et al, 2011) and is well documented in several special issues (ACP, JGR, and Atmospheric Environment). Two days after the first large eruption on 14 April, we detected the ash cloud with a backscatter lidar system over Jülich,western Germany (50 • 54 N,6 • 24 E).…”
Section: Introductionmentioning
confidence: 99%
“…In the atmosphere, sulphur-bearing gases such as SO 2 transformed into tiny sulphuric acid particles 2,44 . Aerosol size distributions within ash clouds showed a fine mode (0.1-0.6 mm) associated with sulphuric acid and/or sulphate, and a coarse mode (0.6-35 mm) associated with ash 45 . Numerous studies showed that the Eyjafjallajökull ash particles were strongly depolarizing 46 and that particles were electrically charged 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…A lognormal distribution has been justified for volcanic ash PSDs for the 2010 Eyjafjallajökull eruption from aircraft measurement (Schumann et al 2011;Johnson et al 2012;Turnbull et al 2012). Although all flights where the ash PSD was measured were during the same eruptive phase, discrepancies exist between PSD parameter measurements, perhaps due to the difference in assumed ash properties and sampling methods used (see Turnbull et al (2012) for full discussion).…”
Section: In Situ Aircraft Measurementmentioning
confidence: 99%
“…The PSD of the volcanic ash was observed to be lognormal during in situ sampling at various dates throughout April and May by the FAAM ) and DLR (Schumann et al 2011) aircrafts, and therefore, a lognormal PSD is used. The average value for the geometric standard deviation given by Johnson et al 2012 (σ g =1.85±0.5, dependent on assumed single scattering properties) is here considered the best approximation to use. Variations in atmospheric water vapour, surface emissivity and plume geometry are not discussed, but this work is well covered by Corradini et al (2008).…”
Section: Case Study: 2010 Eyjafjallajökull Eruptionmentioning
confidence: 99%